Parâmetros moleculares e bioquímicos sobre a exposição per os aguda e crônica a xenobióticos eletrofílicos em insetos-modelos - Piccoli, Bruna Candia (2020)
Continuous exposure to small doses of toxic substances elicit changes in the transcriptional profile and function of proteins before causing physical damage to organisms. Toxic effects can appear even after exposure stops. Knowing the mechanism of action and identifying biomarkers of early substance toxicity are interests of the scientific community. As humans are continually exposed to several xenobiotics, it is necessary to study the effects of concomitant exposure to two or more toxic agents and establish experimental models for translational studies. Xenobiotics like methylmercury (MeHg+) and vinylcyclohexene (VCH) have similar electrophilic properties, albeit their combined toxicity profile has not been assessed. Thus, this work aims to study the effects of per os acute, intermediate and chronic exposure to MeHg+ and the possible reversal of the effects of this xenobiotic after the interruption of exposure in behavioral and biochemical parameters of the Lobster cockroach N. cinerea, as well as the individual and combined effect of MeHg+ and VCH on the transcriptional profile of the fly D. melanogaster since these compounds have similarities in their toxicity mechanisms (affinity for proteins containing –SH and –SeH). Cockroaches were exposed to diets containing 0 (control), 2.5, 25, and 100 μg of MeHg+/g of diet for 10, 30, and 90 days. Additional groups of cockroaches were fed the same doses of MeHg+ for 30 days and then underwent a detoxification period for 60 days. Nymphs exposed to 100 μg MeHg+/g succumbed to a high mortality rate, along with biochemical changes (increased production of reactive oxygen species and activity of glutathione S-transferase, as well as decreased acetylcholinesterase activity) and behavioral changes. We observed delayed mortality and behavioral changes in nymphs exposed to 100 μg MeHg+/g for 30 days with a subsequent 60 day detoxification period. To evaluate the transcriptional profile of D. melanogaster, RNA-sequencing of exposed flies was performed individually and concurrently at 1 mM VCH and 200 μM MeHg+ for three days. The VCH deregulated 38 genes (most of which were overexpressed), while MeHg+ altered 26 genes (14 down-regulated genes). The co-exposure of the VCH + MeHg+ altered 72 genes with a greater number of down-regulated genes. These results suggest that, although the compounds might have some similar protein targets, the transcriptional profile after individual exposures and co-exposure was different. The set of proteins that contains –SH and –SeH was explored and we identified thioredoxin, glutaredoxin, glutathione S-transferase, and glucose dehydrogenase as targets for VCH and/or MeHg+. Together, these data suggest that the use of insects in the study of compound toxicity is relevant, with D. melanogaster being widely used in research and N. cinerea being validated as a potential experimental organism for translational studies. We also indicate possible targets for MeHg+ and VCH that may be potential biomarkers of early toxicity to these xenobiotics.